Räumliche Auswirkungen der Internationalisierung in der Automobilindustrie - Gaebe, Wolf (ERDKUNDE, 1991)
Firms' strategies in the automobile industry cannot be explained by a single theoretical concept. Various models, which explain locational requirements and conditions (marketing theories, product cycle theory and theories concerning the international division of labour), and production and logistics systems are needed. The locational pattern of the japanese automobile industry is based on lean production and on securing and increasing market share, the locational pattern of General Motors and Ford on the Fordist model and on cast reduction by way of the international division of labour. Locational organization of the European automobile industry is strongly related to national production and logistics systems. While the specialists, producers of luxury cars, follow an export-orientated strategy, Opel and Ford comply with the worldwide cast and production-orientated locational structure of the US firms, VW makes vehicles for different market segments and regional markets and thus follows a market-orientated strategy. The Italian and French automobile industries, on the other hand, try to ensure locational and market positions with a cost-orientated strategy (automation and rationalization). Following japan's example, new forms of labour and production organization are being introduced, especially in Europe, which combine the advantages of craftsmanship (product differentiation and high quality) with modern mass production (low unit casts).